Prevalence and risk factors of sarcopenia in patients with cirrhosis – an observational study - Abdul Majeed, Ammara; Hafeezullah Shaikh; Abdur Rasheed; Raheela Khalid; Fakhar Ali Qazi Arisar; Hafsa Ghias (Journal of the Pakistan Medical Association, 2023)
Objectives: To identify the prevalence and predictors of sarcopenia in cirrhotic patients. Method: The observational, cross-sectional study was conducted at the National Institute of Liver and Gastrointestinal Diseases, Karachi, from January 30 to July 31, 2021, and comprised cirrhotic patients of either gender aged 18-60 years. Clinical and laboratory data was recorded for each patient. Body weight was adjusted for ascites. Sarcopenia was determined based on the Asian Working Group for Sarcopenia-2019 guideline via hand grip strength and chair standing. Independent predictors for sarcopenia were identified. Data was analysed using SPSS 26. Results: Out of 434 cirrhotic patients assessed, 386(89%) were enrolled. Of them, 237(61.4%) were males, 149(38.6%) were females, 327(84.7%) were aged >45 years and 201(52.1%) had moderate professional activity. Sarcopenia was detected in 314(81.3%) patients; 185(59%) males and 129(41%) females. Age, chair exercise and hand grip scores as well as haemoglobin, albumin and potassium levels were significantly associated with sarcopenia (p<0.05) Conclusion: Sarcopenia was found to be very common in patients with cirrhosis. Increasing age, concomitant comorbidities, and presence of liver decompensation increased the risk of sarcopenia. Key Words: End-stage liver disease, Hand strength, Frailty, Potassium, Serum albumin.